Environmentally friendly starch-based adhesives for bonding high-performance wood composites: a review - Maulana, Muhammad Iqbal; Lubis, Muhammad Adly Rahandi; Febrianto, Fauzi; Lee, Seng Hua; Iswanto, Apri Heri; Antov, Petar; Kristak, Lubos; Efri Mardawati; Rita Kartika Sari; Zaini, Lukmanul Hakim; Hidayat, Wahyu; Giudice, Valentina Lo; et al. (Multidisciplinary Digital Publishing Institute, 2022)
In recent years, bio-based wood adhesives have gained an increased industrial and research interest as an environmentally friendly and renewable alternative to the commercial petroleum-based synthetic adhesives used in the wood-based industry. Due to its renewability, abundance, relatively low price, and good adhesion properties, starch is a promising natural feedstock for synthesizing bio-based adhesives for wood-based composites. This review aims to summarize the recent advances in developing sustainable starch-based wood adhesives for manufacturing non-toxic, low-emission wood composites with enhanced properties and lower environmental impact. Recent developments in starch modification, physical, and enzymatic treatments applied to improve the performance of starch-based wood adhesives, mainly in terms of improving their water resistance and bonding strength, are also outlined and discussed.